2023
DOI: 10.1038/s41467-023-39235-5
|View full text |Cite|
|
Sign up to set email alerts
|

Multi-layered cement-hydrogel composite with high toughness, low thermal conductivity, and self-healing capability

Abstract: The inherent quasi-brittleness of cement-based materials, due to the disorder of their hydration products and pore structures, present significant challenges for directional matrix toughening. In this work, a rigid layered skeleton of cement slurry was prepared using a simplified ice-template method, and subsequently flexible polyvinyl alcohol hydrogel was introduced into the unidirectional pores between neighboring cement platelets, resulting in the formation of a multi-layered cement-based composite. A tough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 67 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…The CVFF force field has been proved to be an effective empirical force field for analyzing the interactions between atoms of polar molecular, CLAYFF force field often being used to describe the interface structure of cement matrix and water molecules. CVFFF and CLAYFF was combined used to describe the polar molecular and cement mineral system. , Therefore, this paper uses CVFF to describe CNC molecule and employs CLAYFF for CNC/C–S–H interfacial simulation. The detailed parameters of CVFF and CLAYFF are referred to and, respectively.…”
Section: Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The CVFF force field has been proved to be an effective empirical force field for analyzing the interactions between atoms of polar molecular, CLAYFF force field often being used to describe the interface structure of cement matrix and water molecules. CVFFF and CLAYFF was combined used to describe the polar molecular and cement mineral system. , Therefore, this paper uses CVFF to describe CNC molecule and employs CLAYFF for CNC/C–S–H interfacial simulation. The detailed parameters of CVFF and CLAYFF are referred to and, respectively.…”
Section: Simulationmentioning
confidence: 99%
“…The interatomic distance affects the lifetime of the hydrogen bonds. Time correlation function (TCF) can analyze the stability of hydrogen bonds, a larger TCF means a more stable bonding. , As Figure shows, the stability of hydrogen bonds formed by CNCs follows the order that –COO – > –OH > –NH 2 > –SO 3 – . RDF analysis suggested that the atoms at CNC-C/C–S–H interface have the closest spatial correlation, and the distance between atoms affects the electrostatic adsorption; therefore, the hydrogen bond formed by CNC-C has the most stable performance.…”
Section: Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 To enhance the mechanical stability, a "soft-hard synergistic" strategy can be employed whereby reinforcement materials are incorporated as rigid fillers into a soft amorphous matrix, resulting in a soft-hard dual-network structure. 22 Through the synergistic interplay between the rigid and soft components, material stress energy is dissipated significantly, thereby enhancing resistance to deformation and fracture. However, the contribution of this toughening method for improving mechanical performance is limited.…”
Section: Introductionmentioning
confidence: 99%
“…ceramics, glasses, and cements, usually have high mechanical strength but low toughness. 1 An elaborate incorporation of organic components into the inorganic matrix can substantially improve the toughness of the composites, meanwhile maintaining their high strength. For instance, the toughness of seashells is around 3 orders of magnitude higher than that of their component CaCO 3 crystals (aragonite), which results from the unique brick-mud arrangement, and organic polymers interspersed between the inorganic layers.…”
Section: Introductionmentioning
confidence: 99%